2015
DOI: 10.1177/1721727x15618671
|View full text |Cite|
|
Sign up to set email alerts
|

Study on anti-inflammatory and immunomodulatory effects of fluoxetine in rat models of inflammation

Abstract: The aim of the present study was to evaluate the anti-inflammatory effect of fluoxetine in carrageenan-and lipoplysaccharideinduced models of inflammation by investigating the changes in serum levels of pro-inflammatory cytokine TNF-α and anti-inflammatory cytokines IL-10 and TGF-β after single and repeated administration of the drug. To study the effect of a single and repeated dose fluoxetine on carrageenan-induced paw edema male Wistar rats were divided into five groups (n = 8): control group; positive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Previous research reported that Flu relieved the behavioral changes and improved the structural deteriorations that occurred in the hippocampal regions of mice exposed to CUMS in accordance with our results (CB Filho et al, 2015;Ali et al, 2017;Ayuob et al, 2018). Although some studies have reported that Flu has anti-inflammatory activity (Kostadinov et al, 2015) and antioxidant properties (Caiaffo et al, 2016), in this study, administration of Flu has not been associated with a significant changes in proinflammatory cytokines or antioxidant levels. This might be attributed to the relatively short time of Flu administration.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research reported that Flu relieved the behavioral changes and improved the structural deteriorations that occurred in the hippocampal regions of mice exposed to CUMS in accordance with our results (CB Filho et al, 2015;Ali et al, 2017;Ayuob et al, 2018). Although some studies have reported that Flu has anti-inflammatory activity (Kostadinov et al, 2015) and antioxidant properties (Caiaffo et al, 2016), in this study, administration of Flu has not been associated with a significant changes in proinflammatory cytokines or antioxidant levels. This might be attributed to the relatively short time of Flu administration.…”
Section: Discussionsupporting
confidence: 90%
“…Of interest, MIF could also regulate a plethora of cytokines as it has been revealed in our pathway analysis ( Figure 5B). It is possible that clomipramine acutely elevated the levels of cortisol or induced anti-inflammatory cytokine secretion (e.g., interleukin-10 in the serum), as described before [77], and our finding on the elevated level of MIF represents a long-term compensatory mechanism against the triggered changes by adulthood.…”
Section: Mif Hypothalamic-pituitary-adrenal Axis and Inflammationmentioning
confidence: 56%
“…regarding the influence of fluoxetine on TNF-α in different models of inflammation including acting via the immunosuppressant properties of serotonin, inhibition of the transcription factor NF-κB and inhibition of the phosphorylation of p38 MAPK, or potentially acting as a serotonin antagonist on 5-HT2A receptors (Kostadinov et al, 2015). The present study does not provide data to enable the elucidation of the role of serotonin or the other mentioned pathways' participation in our model.…”
Section: Discussionmentioning
confidence: 80%
“…It is apparent that fluoxetine can have different effects in different experimental models. For example, fluoxetine reduced TNF-α production in LPS-induced inflammation in rats, and also had an inhibitory effect in carrageenan-induced inflammation following multiple doses, but enhanced TNF-α production in the same model if only given as a single dose (Kostadinov et al, 2015). Hence it is apparent that the dose, frequency/duration of administration and model of inflammation will lead to contrasting observations in relation to the effects of fluoxetine on TNF-α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation